Evaluación del semen bovino, pos descongelación según temperaturas de transporte - García Sánchez, Priscila Salomé (2015)
The present research was made at the Biotechnology Center Laboratory of Animal Reproduction of the National University of Loja, with the purpose to study protocols of transport temperatures in semen straws that do not involve the use of liquid nitrogen, evaluating the quality, at different intervals of transport times. The first protocol was to transport the semen straw to cooling temperature between 1,5 and 5°C, the second at 18°C , and the third at 38°C of temperature. 20 semen straws were evaluated in each protocol. The evaluation of each one of the protocols was made at 30, 45 and 60 minutes time in which the semen straw can be transported in order to obtain optimum results. There were studied the following variables: individual motility, live sperm, dead and abnormal ones. For the interpretation and analysis of the results it was used a completely randomized design with factorial arrangement 3 x3. Results showed that the best percentages of individual motility and survival was obtained in Protocol A ( temperature between 1,5 and 5 °C), also in this protocol no sudden changes in temperature was noticed, as from 30 minutes the temperature was maintained at 1,8°C up to 60 minutes. In the three stages of transportation acceptable quality values of sperm were obtained. The variables recorded at 60 minutes were: 58% individual motility; 59,2% survival and abnormal sperm 10,7% very acceptable sperm for thawed semen. It is concluded that the best method of transport sperm after being freezing is to place the semen straw that is extracted from the nitrogen tank in the thermoses covered internally with froth of polyurethane and coated in ice blocks and cooled water between 1,5 and 5°C.